Extracellular electron transfer by the cultured coral photosymbiont Symbiodinium microadriaticum - Loris Marcel; James T. Simon; Joshua M. Lawrence; Svetlana Menkin; Adrian C. Barbrook; R. Ellen R. Nisbet; Christopher J. Howe; Jenny Z. Zhang (Photosynthesis Research, 2026)
Photosynthetic microorganisms may show extracellular electron transfer (EET), in which some of the electrons generated by photosynthesis or respiration are lost from the cell. Most studies have focussed on cyanobacteria, with very few on eukaryotic algae. Here we demonstrate EET from the eukaryotic dinoflagellate alga Symbiodinium microadriaticum , a species that can form symbiosis with corals and other Cnidaria. We show that the EET involves diffusible electroactive species, which may represent a previously unsuspected route for communication between symbionts and hosts. We show that EET can be used to study photosynthetic and respiratory functions in the dinoflagellate. We also show that it can provide information on the effects of environmental stresses including changes in temperature (linked to coral bleaching), pH and light intensity. The electrochemical platform outlined in this study offers a novel tool for studying dinoflagellate physiology, the coral-dinoflagellate symbiosis, and the molecular mechanisms of bleaching.

Taking Genomics Outdoors: Linking Local Adaptation, Trait Variation and Gene Expression in Grass Ecotypes Across a Rainfall Gradient - Jack Sytsma; Matthew Galliart; Kian Fogarty; Kori Howe; Bradley J. S. C. Olson; Sara G. Baer; David J. Gibson; Brian Maricle; Eli Hartung; Loretta Johnson (Molecular Ecology, 2026)
With increasing droughts, understanding local adaptation and drought tolerance in ecologically dominant species is crucial for enhancing ecosystem resilience. We leveraged a long‐term reciprocal garden to assess local adaptation and drought responses in Andropogon gerardi , a foundation grassland species in the US Great Plains. Our objectives were to identify adaptive traits, explore gene expression responses across a rainfall gradient and under experimental drought, and integrate trait‐based analyses with gene expression profiles to test for local adaptation. Reciprocal gardens, established a decade ago, are composed of different A. gerardi ecotypes sourced along a rainfall gradient (MAP 480–1167 mm year. −1 ) and sown as ecological communities. Rainout shelters imposed experimental drought. We hypothesized that ecotypes should perform best in their homesite, reflecting local adaptation. The dry ecotype should perform best under rainouts and exhibit traits and expression profiles favouring drought tolerance; the wet ecotype should favour traits and gene expression enhancing growth and resource acquisition. We found ecotypes had highest biomass and cover in their homesite, confirming local adaptation. The dry ecotype showed stress‐tolerance strategies (shorter, more water‐efficient, upregulated drought‐response genes), while the wet ecotype emphasized growth strategies (taller, higher biomass, upregulation of growth hormones). Using co‐expression networks, gene clusters linked adaptive traits, revealing genetic mechanisms of adaptation. Together, our results demonstrate that dry ecotypes maintain productivity under water limitation through coordinated physiological and transcriptomic stress‐tolerance strategies, whereas wet ecotypes achieve higher productivity only under high‐moisture conditions. We provide strong support for climate‐matched ecotypes to improve grassland restoration and resilience under increasing drought.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

Forest restoration can bolster salmon population persistence under climate change - Michele S. Buonanduci; Eric R. Buhle; Michael J. Case; Emily R. Howe; James C. Robertson; Nicholas VanBuskirk; Ailene K. Ettinger (Biological Conservation, 2025)

Dinoflagellate chloroplasts as a model for extreme genome reduction and fragmentation in organelles – The COCOA principle for gene retention - Christopher J. Howe; Adrian C. Barbrook (Protist, 2024)

The test–retest reliability of physiological and perceptual responses during treadmill load carriage - Danielle M. Vickery-Howe; Ben J. Dascombe; Anthea C. Clarke; Jace R. Drain; Minh Huynh; Kane J. Middleton (European Journal of Applied Physiology, 2024)
Purpose Understanding the test–retest reliability of physiological responses to load carriage influences the interpretation of those results. The aim of this study was to determine the test–retest reliability of physiological measures during loaded treadmill walking at 5.5 km h −1 using the MetaMax 3B. Methods Fifteen Australian Army soldiers (9 male, 6 female) repeated two 12-min bouts of treadmill walking at 5.5 km h −1 in both a 7.2 kg Control condition (MetaMax 3B, replica rifle) and a 23.2 kg Patrol condition (Control condition plus vest) across three sessions, separated by one week. Expired respiratory gases and heart rate were continuously collected, with the final 3 min of data analysed. Ratings of Perceived Exertion and Omnibus-Resistance Exercise Scale were taken following each trial. Reliability was quantified by coefficient of variation (CV), intra-class correlation coefficients (ICC), smallest worthwhile change (SWC), and standard error of the measurement. Results Metabolic and cardiovascular variables were highly reliable (≤ 5% CV; excellent-moderate ICC), while the respiratory variables demonstrated moderate reliability (< 8% CV; good-moderate ICC) across both conditions. Perceptual ratings had poorer reliability during the Control condition (12–45% CV; poor ICC) than the Patrol condition (7–16% CV; good ICC). Conclusions The test–retest reliability of metabolic and cardiovascular variables was high and relatively consistent during load carriage. Respiratory responses demonstrated moderate test–retest reliability; however, as the SWC differed with load carriage tasks, such data should be interpreted independently across loads. Perceptual measures demonstrated poor to moderate reliability during load carriage, and it is recommended that they only be employed as secondary measures. Graphical abstract

Characterization of recent wild pig-vehicle collisions in Georgia, USA - Jeremiah L. Psiropoulos; Emily Howe; John J. Mayer; Sophie C. McKee (Mammal Research, 2024)

Periconceptional and Prenatal Exposure to Metals and Extracellular Vesicle and Particle miRNAs in Human Milk: A Pilot Study - Caitlin G. Howe; David A. Armstrong; Meghan E. Muse; Diane Gilbert-Diamond; Jiang Gui; Anne G. Hoen; Thomas J. Palys; Roxanna L. Barnaby; Bruce A. Stanton; Brian P. Jackson; Brock C. Christensen; Margaret R. Karagas (Exposure and Health, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Performance determinants, running energetics and spatiotemporal gait parameters during a treadmill ultramarathon - Christopher C. F. Howe; Nicola Swann; Owen Spendiff; Anna Kosciuk; Elizabeth K. L. Pummell; Hannah J. Moir (European Journal of Applied Physiology, 2021)
Purpose The objective of this study was to investigate the changes in metabolic variables, running energetics and spatiotemporal gait parameters during an 80.5 km treadmill ultramarathon and establish which key predictive variables best determine ultramarathon performance. Methods Twelve participants (9 male and 3 female, age 34 ± 7 years, and maximal oxygen uptake ( $$\dot{V}$$ V ˙ O 2max ) 60.4 ± 5.8 ml·kg −1 ·min −1 ) completed an 80.5 km time trial on a motorised treadmill in the fastest possible time. Metabolic variables: oxygen consumption ( $$\dot{V}$$ V ˙ O 2 ), carbon dioxide production ( $$\dot{V}$$ V ˙ CO 2 ) and pulmonary ventilation ( $$\dot{V}$$ V ˙ E ) were measured via indirect calorimetry every 16.1 km at a controlled speed of 8 km·h −1 and used to calculate respiratory exchange ratio (RER), the energy cost of running (Cr) and fractional utilisation of $$\dot{V}$$ V ˙ O 2max ( F ). Spatiotemporal gait parameters: stride length (SL) and cadence (SPM) were calculated via tri-axial accelerometery. Results Trial completion time was 09:00:18 ± 01:14:07 (hh:mm:ss). There were significant increases in $$\dot{V}$$ V ˙ O 2 , Cr, F , $$\dot{V}$$ V ˙ E and heart rate (HR) ( p < 0.01); a significant decrease in RER ( p < 0.01) and no change in SL and SPM ( p > 0.05) across the measured timepoints. F and Cr accounted for 61% of the variance in elapsed finish time ( $$R_{{{\text{adj}}}}^{{2}}$$ R adj 2 = 0.607, p < 0.01). Conclusion A treadmill ultramarathon elicits significant changes in metabolic variables, running energetics and spatiotemporal gait parameters. With F and Cr explaining 61% of variance in finish time. Therefore, those able to maintain a higher F , while adopting strategies to minimise an increase in Cr may be best placed to maximise ultramarathon performance.

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke - Matthew D. Howe; J. Weldon Furr; Yashasvee Munshi; Meaghan A. Roy-O’Reilly; Michael E. Maniskas; Edward C. Koellhoffer; John d’Aigle; Lauren H. Sansing; Louise D. McCullough; Akihiko Urayama (GeroScience, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Generation of transgenic goats by pronuclear microinjection: a retrospective analysis of a commercial operation (1995–2012) - W. Gavin; S. Blash; N. Buzzell; D. Pollock; L. Chen; N. Hawkins; J. Howe; K. Miner; J. Pollock; C. Porter; M. Schofield; Y. Echelard; et al. (Transgenic Research, 2018)

Multiple paternity in a Pacific marine turtle population: maternal attributes, offspring outcomes and demographic inferences - M. Howe; N. N. FitzSimmons; C. J. Limpus; S. M. Clegg (Marine Biology, 2018)

Influence of Local, Landscape, and Regional Variables on Sedge and Marsh Wren Occurrence in Great Lakes Coastal Wetlands - Hannah G. Panci; Gerald J. Niemi; Ronald R. Regal; Douglas C. Tozer; Thomas M. Gehring; Robert W. Howe; Christopher J. Norment (Wetlands, 2017)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

A comparative approach to assess drivers of success in mammalian conservation recovery programs - Jennifer J. Crees; Amy C. Collins; P. J. Stephenson; Helen M. R. Meredith; Richard P. Young; Caroline Howe; Mark R. Stanley Price; Samuel T. Turvey (Conservation Biology, 2016)
The outcomes of species recovery programs have been mixed; high‐profile population recoveries contrast with species‐level extinctions. Each conservation intervention has its own challenges, but to inform more effective management it is imperative to assess whether correlates of wider recovery program success or failure can be identified. To contribute to evidence‐based improvement of future conservation strategies, we conducted a global quantitative analysis of 48 mammalian recovery programs. We reviewed available scientific literature and conducted semistructured interviews with conservation professionals involved in different recovery programs to investigate ecological, management, and political factors associated with population recoveries or declines. Identifying and removing threats was significantly associated with increasing population trend and decreasing conservation dependence, emphasizing that populations are likely to continue to be compromised in the absence of effective threat mitigation and supporting the need for threat monitoring and adaptive management in response to new and potential threats. Lack of habitat and small population size were cited as limiting factors in 56% and 42% of recovery programs, respectively, and both were statistically associated with increased longer term dependence on conservation intervention, demonstrating the importance of increasing population numbers quickly and restoring and protecting habitat. Poor stakeholder coordination and management were also regularly cited by respondents as key weaknesses in recovery programs, indicating the importance of effective leadership and shared goals and management plans. Project outcomes were not influenced by biological or ecological variables such as body mass or habitat, which suggests that these insights into correlates of conservation success and failure are likely to be generalizable across mammals.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

Development of an Integrated Surface Stimulation Device for Systematic Evaluation of Wound Electrotherapy - D. S. Howe; J. Dunning; C. Zorman; S. L. Garverick; K. M. Bogie (Annals of Biomedical Engineering, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Assessing S ymbiodinium diversity in scleractinian corals via next‐generation sequencing‐based genotyping of the ITS2 rDNA region - Chatchanit Arif; Camille Daniels; Till Bayer; Eulalia Banguera‐Hinestroza; Adrian Barbrook; Christopher J. Howe; Todd C. LaJeunesse; Christian R. Voolstra (Molecular Ecology, 2014)
The persistence of coral reef ecosystems relies on the symbiotic relationship between scleractinian corals and intracellular, photosynthetic dinoflagellates in the genus Symbiodinium . Genetic evidence indicates that these symbionts are biologically diverse and exhibit discrete patterns of environmental and host distribution. This makes the assessment of Symbiodinium diversity critical to understanding the symbiosis ecology of corals. Here, we applied pyrosequencing to the elucidation of Symbiodinium diversity via analysis of the internal transcribed spacer 2 ( ITS 2) region, a multicopy genetic marker commonly used to analyse Symbiodinium diversity. Replicated data generated from isoclonal Symbiodinium cultures showed that all genomes contained numerous, yet mostly rare, ITS 2 sequence variants. Pyrosequencing data were consistent with more traditional denaturing gradient gel electrophoresis ( DGGE ) approaches to the screening of ITS 2 PCR amplifications, where the most common sequences appeared as the most intense bands. Further, we developed an operational taxonomic unit ( OTU )‐based pipeline for Symbiodinium ITS 2 diversity typing to provisionally resolve ecologically discrete entities from intragenomic variation. A genetic distance cut‐off of 0.03 collapsed intragenomic ITS 2 variants of isoclonal cultures into single OTU s. When applied to the analysis of field‐collected coral samples, our analyses confirm that much of the commonly observed Symbiodinium ITS 2 diversity can be attributed to intragenomic variation. We conclude that by analysing Symbiodinium populations in an OTU ‐based framework, we can improve objectivity, comparability and simplicity when assessing ITS 2 diversity in field‐based studies.

Polyuridylylation and processing of transcripts from multiple gene minicircles in chloroplasts of the dinoflagellate Amphidinium carterae - Adrian C. Barbrook; Richard G. Dorrell; Jennifer Burrows; Lindsey J. Plenderleith; R. Ellen R. Nisbet; Christopher J. Howe (Plant Molecular Biology, 2012)

Genetic diversity and phylogeography of broomcorn millet ( Panicum miliaceum L.) across Eurasia - HARRIET V. HUNT; MICHAEL G. CAMPANA; MATTHEW C. LAWES; YONG‐JIN PARK; MIM A. BOWER; CHRISTOPHER J. HOWE; MARTIN K. JONES (Molecular Ecology, 2011)

Molecular mapping of adult plant stripe rust resistance in wheat and identification of pyramided QTL genotypes - H. S. Bariana; U. K. Bansal; A. Schmidt; A. Lehmensiek; J. Kaur; H. Miah; N. Howes; C. L. McIntyre (Euphytica, 2010)

How spatially coherent and statistically robust are temporal changes in extreme precipitation in the contiguous USA? - S. C. Pryor; J. A. Howe; K. E. Kunkel (International Journal of Climatology, 2009)
Century‐long precipitation records from stations in the contiguous USA indicate an increased frequency of rainy days over the past century and some evolution in the probability distributions of precipitation amount. Temporal trends in eight metrics of the precipitation climate are of similar magnitude and sign regardless of whether they are derived from bootstrapping of regression residuals or using the Kendall's tau statistic, though the bootstrap technique generally resolved a larger number of ‘significant’ trends. There is substantial variability in terms of the magnitude, significance and sign of the linear trends with specific metrics, and they are sensitive to recording bias of light precipitation events in the early part of the 20th century. The majority of stations that exhibit significant linear trends show evidence of increases in the intensity of events above the 95th percentile. The resolved trends tend to have a larger magnitude at the end of the century. Spatial variability as manifest in the spatial autocorrelation in the interannual variability and trends in extreme metrics is manifest at a range of scales, but in general the correlation between stations is significant only for separation of distances of a few tens of kilometres. The largest trends towards increased annual total precipitation, number of rainy days and intense precipitation (e.g. fraction of precipitation derived from events in excess of the 90th percentile value) are focussed on the Central Plains/northwestern Midwest. Copyright © 2008 Royal Meteorological Society

Dynamics of Campylobacter colonization of a natural host, Sturnus vulgaris (European Starling) - F. M. Colles; N. D. McCarthy; J. C. Howe; C. L. Devereux; A. G. Gosler; M. C. J. Maiden (Environmental Microbiology, 2009)
Summary Wild European Starlings ( Sturnus vulgaris ) shed Campylobacter at high rates, suggesting that they may be a source of human and farm animal infection. A survey of Campylobacter shedding of 957 wild starlings was undertaken by culture of faecal specimens and genetic analysis of the campylobacters isolated: shedding rates were 30.6% for Campylobacter jejuni , 0.6% for C. coli and 6.3% for C. lari. Genotyping by multilocus sequence typing (MLST) and antigen sequence typing established that these bacteria were distinct from poultry or human disease isolates with the ST‐177 and ST‐682 clonal complexes possibly representing starling‐adapted genotypes. There was seasonal variation in both shedding rate and genotypic diversity, both exhibiting a maximum during the late spring/early summer. Host age also affected Campylobacter shedding, which was higher in younger birds, and turnover was rapid with no evidence of cross‐immunity among Campylobacter species or genotypes. In nestlings, C. jejuni shedding was evident from 9 days of age but siblings were not readily co‐infected. The dynamics of Campylobacter infection of starlings differed from that observed in commercial poultry and consequently there was no evidence that wild starlings represent a major source of Campylobacter infections of food animals or humans.

Genetic diversity across the range of a temperate lizard - Briar J. Howes; Stephen C. Lougheed (Journal of Biogeography, 2008)
Aim To examine range‐wide patterns of genetic diversity in association with range limits in a broadly distributed temperate lizard, and to identify the contributions of a series of environmental, geographical and historical variables to the observed patterns. Reduced genetic diversity may limit local adaptation in peripheral populations, thereby limiting their ability to adapt to marginal environmental conditions, possibly explaining the existence of temporally stable range limits. Location Various sampling locales throughout eastern and central USA and southern Ontario, Canada. Methods Genetic diversity of nuclear DNA microsatellites was estimated for each of 38 populations from across the range of eastern North America’s most broadly distributed lizard, the five‐lined skink, Plestiodon fasciatus (Linnaeus, 1758). Results Local climatic conditions and an interaction between distance from range border and glaciation history best predicted a population’s present‐day genetic diversity. Overall, peripheral populations had reduced genetic diversity relative to that of central populations, but this difference was attributable to the reduced genetic diversity in peripheral populations to the north and west that are not bordered by any obvious physical boundaries. Main conclusions Some, but not all, peripheral populations had reduced genetic diversity relative to that of more central populations, which probably arose through an interaction of ecological and historical factors. Peripheral populations that were bordered by an obvious boundary (e.g. an ocean) had higher diversity than peripheral populations that were not bordered by an obvious physical barrier to range expansion, suggesting that reduced intrapopulation genetic diversity is associated with range limits in the five‐lined skink.

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Integrated Measures of Anthropogenic Stress in the U.S. Great Lakes Basin - Nicholas P. Danz; Gerald J. Niemi; Ronald R. Regal; Tom Hollenhorst; Lucinda B. Johnson; JoAnn M. Hanowski; Richard P. Axler; Jan J. H. Ciborowski; Thomas Hrabik; Valerie J. Brady; John R. Kelly; John A. Morrice; et al. (Environmental Management, 2007)

Mouse leukaemia, a dichotomy of virus neutralizing and cytotoxic antibodies - J. G. Sinkovics; C. C. Shullenberger; C. D. Howe; Barbara A. Bertin (Archives of Virology, 1966)